Formação para a participação: perspectivas freireanas para a educação infantil no município de Diadema, São Paulo - Oliveira, Solange de Lima (2008)
The theme of this Dissertation is educating for participation within the public school. Its object is to influence the thinking of Paulo Freire in politics curricular Childhood Education in the municipality of Diadema. Specifically, this work propose to answer the following question: How does the education for participation, announced in the proposed Child Rearing of Diadema, is being implemented? Among the researched subjects are: historical context of the city formation, built as a result of important social achievements and difficulties the current educational context; the process of Reorientation of the children's Educational Program under implementation phase and the experience of the Conselho Mirim developed as a space used by citizen's to exercise their citizenship. This empirical research looks into how citizen's formation for participation, implicitly announced in Diadema's children's Educational programme proposal, is being achieved. The collection and analysis and documentary studies as well as observations and semi-structured interviews, demonstrate the importance of a democratic, participating, competent and happy school, where educators and families value dialogue and learn about how children think of and feel about the school and the learning process, and know when they are listened to and cared for, they can feel capable and willing to learn and participate as reality modifiers. This research allowed conclude on the relevance and the possibility to educate for participation in the Children's Education, with benchmarks freireanos. This demonstrated that this practice depended on the political-educational option of educators of secretary of education in the municipality of Diadema. The Henfil EMEI, with all of its educators, students and family, is demonstrating that the democratic ideals of education can become a dream possible